2005
DOI: 10.1152/ajplung.00380.2003
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 may mediate allergen-induced hyperresponsiveness independently of IL-5 or eotaxin by effects on airway smooth muscle

Abstract: IL-13 is a mediator of allergen-induced airway hyperresponsiveness (AHR). The aim of this study was to evaluate whether eotaxin and IL-5 were implicated in the effects of IL-13 on allergen-induced AHR or whether IL-13 may exert its effects through direct actions on airway smooth muscle (ASM). To study this question airway inflammation and AHR were induced in mice by sensitization and subsequent challenge on three successive days with ovalbumin. A monoclonal anti-IL-13 antibody administered before each challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 34 publications
3
60
0
Order By: Relevance
“…IL-13 is a pleiotropic cytokine produced mainly by T cells and is critical for the development of airway hyperresponsiveness (AHR) associated with allergen exposure [18]. It has indeed been reported that treatment of mice with anti-IL-13 mAb inhibited AHR [19,20] and that Il-13-induced airway inflammation might involve a direct effect on airway smooth muscles [21]. Our results strongly suggest that IL-13 production is intrinsically different in the two mouse strains and accounts for the increased bronchial hyperresponsiveness in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-13 is a pleiotropic cytokine produced mainly by T cells and is critical for the development of airway hyperresponsiveness (AHR) associated with allergen exposure [18]. It has indeed been reported that treatment of mice with anti-IL-13 mAb inhibited AHR [19,20] and that Il-13-induced airway inflammation might involve a direct effect on airway smooth muscles [21]. Our results strongly suggest that IL-13 production is intrinsically different in the two mouse strains and accounts for the increased bronchial hyperresponsiveness in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are also a major source of IL-4, which is increased in those mice after allergen exposure [26]. Nevertheless, other factors than IL-13 or mediators released by mast cells could take part in the hyperresponsiveness in mice since two distinct quantitative trait loci (QTL) for susceptibility to allergen-induced airway hyperresponsiveness, Abhr1 (allergen-induced bronchial hyperresponsiveness) and Abhr2, have been identified on chromosome 2 in backcross progeny from A/J and C3H/HeJ mice [21], suggesting that some genetic factors are also important in the pathogenesis of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of Mfge8 around smooth muscle and the lack of Mfge8 in the airway epithelium suggested that the effect of Mfge8 on ASM was independent of interactions between ASM and the adjacent epithelium. However, IL-13 affects the airway epithelium (25) and ASM (26), and airway epithelium has an inhibitory effect on ASM contraction (27,28). To investigate whether smooth muscle-epithelial interactions were important for the function of Mfge8 in ASM contraction, we repeated the tracheal ring contraction assay after denuding the epithelium layer from each ring (4).…”
Section: Effect Of Mfge8 On Tracheal Asm Contraction Is Independent Omentioning
confidence: 99%
“…Ultimately, these processes lead to helper T type 2 (Th2) cell differentiation and further production of the Th2 cytokines IL-4, IL-5, and IL-13 (4-6), and memory T and B cells are generated that can lead to chronic inflammation. Much of the remodeling and dysfunction in resident lung cells that are associated with asthma can be reproduced by IL-13 exposure, including goblet cell metaplasia (7), subepithelial fibrosis (8), and airway hyperresponsiveness (9)(10)(11)(12). IL-4 can mimic many of the effects of IL-13 and is thought particularly important in IgE class switching by B cells.…”
mentioning
confidence: 99%